Conference report : . Report of the annual conference of the Labour Party
For additional documents see: Report and balance sheet (ZO 44998), Report of the NEC (ZO 44996) and (ZK 43413), Agenda (ZO 44997) and (ZK 43411), Resolutions (ZO 44999) and (ZK 43412), Composite resolutions (ZO 45021), List of societies (ZO 45020), The Guardian report (ZO 45022), Chairman's adresses (ZO 45023). Title change from (1989): Conference report.